Diagnosis and Assessment of Disease Activity in Takayasu Arteritis: A Childhood Case Illustrating the Challenge. (15th January 2014) - Watson, L.; Brogan, P.; Peart, I.; Landes, C.; Barnes, N.; Cleary, G.
Abstract : Takayasu Arteritis (TA) is a rare, debilitating large vessel vasculitis occurring in patients of all ages, including infants, but the disease most commonly presents in the third decade. Diagnosis is often delayed and consequently TA is associated with significant morbidity and mortality. Accurate methods of monitoring disease activity or damage are lacking and currently rely on a combination of clinical features, blood inflammatory markers, and imaging modalities. In this report we describe a case of a 14-year-old boy with childhood-onset TA who, despite extensive negative investigations, did indeed have on-going active large vessel vasculitis with fatal outcome. Postmortem analysis demonstrated more extensive and active disease than originally identified. This report illustrates and discusses the limitations of current modalities for the detection and monitoring of disease activity and damage in large vessel vasculitis. Clinicians must be aware of these limitations and challenges if we are to strive for better outcomes in TA.